2016
DOI: 10.5539/ibr.v9n6p72
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effects of Job Satisfaction on the Relationship between Personality Traits and Customer-oriented Behavior in the Malaysian Health Tourism Industry

Abstract: This paper aims to analyze the relationship between personality traits, customer-oriented behavior and job satisfaction. Focusing on the moderating role of job satisfaction in enhancing customer oriented behavior, the research was set in the context of Malaysian health tourism industry. The respondents consisted of nurses in health tourism hospitals in Malaysia. A quantitative cross sectional survey method was adopted, coupled with factor analysis and hierarchical regression analysis to analyze the collected d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…On the other hand, numerous studies found E to be positively correlated with job satisfaction. [4,12,13,28,29] is was not the case in our study where E was a significant negative predictor of job satisfaction. Although our study is not the first to report no or negative prediction for E and job satisfaction, [8,30,31] this is nevertheless an interesting finding.…”
Section: Discussioncontrasting
confidence: 66%
“…On the other hand, numerous studies found E to be positively correlated with job satisfaction. [4,12,13,28,29] is was not the case in our study where E was a significant negative predictor of job satisfaction. Although our study is not the first to report no or negative prediction for E and job satisfaction, [8,30,31] this is nevertheless an interesting finding.…”
Section: Discussioncontrasting
confidence: 66%
“…For example, Niu (2014) revealed that job satisfaction has a moderating effect on the link between personality and innovation behavior. Hee and Abidin (2016) also found that job satisfaction has a moderating effect on enhancing the relationship between personality traits and customeroriented behavior. That is, extraverted employees exhibited a higher level of customer-oriented behavior only when they possessed a high level of job satisfaction.…”
Section: Current Researchmentioning
confidence: 88%
“…First, building on the turnover process model proposed by Allisey et al (2014) and Brough and Frame (2004), the test of a mediating mechanism in this study demonstrates the extent to which satisfaction mediates the relationship between distal factors (i.e., attitudinal and environmental factors) and career plan among police cadets. Next, building on the vocational literature (Hee & Abidin, 2016;Niu, 2014;Swider et al, 2011), the test of a moderating mechanism focuses on the possibility that the predictors differ in the relationship with cadets' career plan by the degree of satisfaction. That is, we test the contention that attitudinal and environmental factors have different effects on police cadets with high satisfaction and their counterparts with low satisfaction.…”
Section: Current Researchmentioning
confidence: 99%
See 1 more Smart Citation